2017
DOI: 10.1038/sc.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Testicular responses to hCG stimulation at varying doses in men with spinal cord injury

Abstract: Study design Prospective Objectives To test whether provocative stimulation of the testes identifies men with chronic spinal cord injury (SCI), a population in which serum testosterone concentrations are often depressed, possibility due to gonadal dysfunction. To accomplish this objective, conventional and lower than the conventional doses of human chorionic gonadotropin (hCG) were administered. Methods Thirty men with chronic SCI [duration of injury >1 year; 18 and 65 years old; 16 eugonadal (>12.1 nmol/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“… 18 Because serum T responses to standard hCG stimulation testing was not significantly different for able-bodied or SCI men, regardless of gonadal status, it was suggested that the preponderance of hypogonadism identified in men with SCI is probably associated with hypothalamic-pituitary dysfunction, and not end-organ failure. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Because serum T responses to standard hCG stimulation testing was not significantly different for able-bodied or SCI men, regardless of gonadal status, it was suggested that the preponderance of hypogonadism identified in men with SCI is probably associated with hypothalamic-pituitary dysfunction, and not end-organ failure. 19 …”
Section: Discussionmentioning
confidence: 99%
“… 18 The testicular response to a conventional dose of human chorionic gonadotropin (hCG; 4000 IU) or with lower doses of hCG (400 and 1000) in those with SCI was generally appropriate, regardless of whether the participants had low or normal serum testosterone levels. 18 , 19 Of note, whether an individual with SCI was hypogonadal or eugonadal was not predictive of whether the person would respond with an appropriate clinical response to the standard stimulation dose of hCG. The authors speculated that because peripheral stimulation to hCG was essentially normal in those with SCI that a more subtle central problem due to insufficient hypothalamic drive to gonadotropin release should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…After SCI, 45–60% of men exhibit low T (hypogonadism, T < 300 ng/dL) [ 91 , 92 , 93 ] that results, in-part, from secondary testicular dysfunction [ 94 ] and impairments in the hypothalamic-pituitary axis [ 95 , 96 ]. Hypogonadism is ~four times more prevalent after SCI than in able-bodied men [ 7 ], with T concentrations remaining >25% below that of age-matched healthy men for an extended duration after SCI [ 91 , 97 ].…”
Section: Androgenic Regulation Of Musclementioning
confidence: 99%
“…There is also an association between severity of injury (complete SCI) and an increased risk of hypogonadism ( 44 , 47 ). Bauman et al compared testicular response to human chorionic gonadotropin (hCG) stimulation in SCI men and able bodied men, and found that SCI men had adequate and equal response; thus concluding that the hypogonadal state in SCI is not due to primary testicular failure ( 48 ). Naderi et al also showed that hypogonadism seen in SCI is likely a centrally mediated failure of the hypothalamic-pituitary-testis axis ( 42 ).…”
Section: Testosterone and Scimentioning
confidence: 99%